2017 12th International Scientific and Technical Conference on Computer Sciences and Information Technologies (CSIT) 2017
DOI: 10.1109/stc-csit.2017.8098778
|View full text |Cite
|
Sign up to set email alerts
|

Press F1 for help: Participatory design for dealing with on-line and real life security of older adults

Abstract: Abstract-In this paper we present the report on the design and development of a platform for the intergenerational exchange of favors. This platform was designed using participatory design approach during a 24-hour hackathon by a team consisting of younger programmers and older adults. The findings of this report show that inter-generational cooperation in which the older adults serve as representatives of the end user, not only improves the design and development of the application, but also provides an effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Therefore, in Table 5, we provide a set of questions that need to be addressed to close the gaps in recent IGC studies, allowing researchers to modify these questions to better suit particular research problems. x x [52] x x x x x [46] x x x [61] x x x [96] x [69] x x x X x x [97] x x x [98] x x [50] x x x x x x [59] x x x x x [65] x x x [99] x x [47] x x x x x [100] x [67] x x x x x x [48] x x x x X [53] x x x x X x [63] x x x [32] x x x x [101] x x…”
Section: Conclusion Limitations and Recommendationsmentioning
confidence: 99%
“…Therefore, in Table 5, we provide a set of questions that need to be addressed to close the gaps in recent IGC studies, allowing researchers to modify these questions to better suit particular research problems. x x [52] x x x x x [46] x x x [61] x x x [96] x [69] x x x X x x [97] x x x [98] x x [50] x x x x x x [59] x x x x x [65] x x x [99] x x [47] x x x x x [100] x [67] x x x x x x [48] x x x x X [53] x x x x X x [63] x x x [32] x x x x [101] x x…”
Section: Conclusion Limitations and Recommendationsmentioning
confidence: 99%
“…Research endeavours ought to provide positive examples of engaging older adults, for example in online crowdsourcing, explored by Skorupska et al (2018) or offline volunteering, described by Carroll et al (2012). Such solutions allow older adults' to build on their experience, as explored by Balcerzak et al (2017), while at the same time encouraging them to stay active. For this reason, it is important to get older adults acquainted with technology, and encourage them either with games, as shown by , intergenerational interaction explored by Orzeszek et al (2017) in the context of participatory design and hackathons, as shown by Kopeć et al (2018a) allowing them to even build up to being able to join development teams, according to Kopeć et al (2018b).…”
Section: Related Workmentioning
confidence: 99%
“…This translates into a strong positive motivator, as one of the most common needs expressed by older adults is the need to feel useful, help others and contribute to the common good in a social setting [11]. Additionally, it also uses one of the advantages that older adults hold over the younger generation: their experience, explored for example by Balcerzak et al [9,10]. Just as their vast knowledge of the cultural and historical context had a positive impact on their performance in a historical location based game [31], so can their long time experience with their native language act as an empowering factor, allowing them to feel confident, and competent enough to climb the ladder of ICT proficiency (a benefit they are aware of [7]); eventually even making them ready to join the ICT solution development process, as in the SPIRAL method [33].…”
Section: Challenges Of Empowering Older Adultsmentioning
confidence: 99%